Economic evaluation of irrigated forage production in a beef cattle operation in the semi-arid tropics of northern Australia. (October 2015) - Monjardino, M.; MacLeod, N.; McKellar, L.; Prestwidge, D.
Abstract: Australia's northern beef industry is a significant contributor to regional economies in northern Australia, but is economically challenged by a range of factors including declining real beef prices, limited market opportunities, stalled productivity growth, increasing levels of enterprise debt, and low returns on investment. The long-term viability of the industry depends on achieving herd productivity gains and lifting enterprise profitability. Typical of the northern Australian beef industry, beef enterprises located in the Gulf of Carpentaria river drainage basins or catchments of north-west Queensland rely on extensive grazing of unimproved native pastures. Feed of reasonable quality is relatively plentiful during the annual wet season, but this is typically followed by feed shortages and sharply declining feed quality in the following dry season. Irrigation of some pasturage could potentially increase the availability and quality of dry-season feed and improve the productivity of these cattle enterprises. To explore this issue, an enterprise-scale bio-economic model was employed to consider several development scenarios involving investments in irrigation infrastructure for a case-study beef enterprise located in the Flinders River catchment in north-west Queensland. Our findings showed improvements in key productivity indicators, such as beef turnoff and enterprise profitability for some forage-based irrigation scenarios. However, the capital cost of installing and operating the infrastructure associated with the assumed scale of irrigation development had a significantly negative effect on returns. The findings suggest that investors will need to be judicious with capital expenditure and investment decisions informed by an understanding of the interplay between irrigation water storage size, expected reliability of filling, and the ability to meet seasonal crop water demand. Highlights: NABSA used to evaluate viability of irrigated forage in a beef enterprise of N Australia Productivity indicators improved for some forage-based scenarios. Cost of irrigated forage outweighed economic gain by large margin. High capital cost of irrigation negatively impacted bottom line. Link between demand, supply and storage of water key to investment decisions